Understanding Penetration Testing for Evaluating Vulnerabilities and Enhancing Cyber Security - Rohith Vallabhaneni; Vinod Veeramachaneni (Engineering And Technology Journal, 2024)
In response to the increasing incidence of cyber-attacks, organizations are prioritizing security testing for their software applications and products. Among the most effective methods for identifying vulnerabilities is penetration testing, which involves simulated attacks on systems to uncover weaknesses that could be exploited by malicious actors. This method not only aids in identifying and remediating security flaws but also evaluates a system's ability to withstand unexpected threats. This paper provides an in-depth exploration of penetration testing, detailing its stages, methodologies, and the role of web application firewalls. A penetration test systematically assesses the security of IT infrastructures by exploiting vulnerabilities in systems, applications, and user behaviours. The findings from these tests are essential for IT management, guiding strategic decisions and prioritizing remediation efforts. Ultimately, the primary aim of penetration testing is to evaluate the risk of a system breach and its potential impact on organizational resources and operations.